A family study of bladder exstrophy. - Ives, E (1980)
The families of 102 index patients with bladder exstrophy treated at The Hospital for Sick Children, Great Ormond Street were studied in an attempt to arrive at an empirical risk of recurrence for sibs. Of the 102 patients, 89 had complete exstrophy, eight had partial exstrophy (variant), and five had exstrophy of the cloaca. In all they had 162 sibs, none of whom had bladder exstrophy. The risk to sibs, in this study and from reports by surgeons of sib pairs in their consecutive series, is low and probably less than 1%. There is a suggestion of an increase in central nervous system malformation in sibs as well as in the index patients.